ANALISIS KEBUTUHAN MEDIA BUKU CERITA BERGAMBAR BERBASIS DIGITAL PADA MUATAN PENDIDIKAN PANCASILA DI SEKOLAH - Dwi Kurnia Zamroni, Anisa; Usman, Herlina; Angger Wardhani, Prayuningtyas (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to determine the needs analysis for the development of digital-based picture story book media on the content of Pancasila Education in elementary schools. This research is a type of R&D (Research and Development) development research using the ADDIE development model which consists of Analysis, Design, Development, Implementation and Evaluation. This research uses the first stage of the ADDIE model, namely the analysis stage. Needs analysis was carried out through literature studies and field studies. The instrument used was a questionnaire in the form of a Google form. The data obtained was then analyzed using descriptive statistical data analysis techniques. The research results show that there is a need to develop learning media for Pancasila education material in the form of digital-based picture story books.